Comparison Between Swenson and Soave-Boley Procedure in the Management of Hirschsprungâs Disease - Chowdhury, ASM Lokman Hossain; Karim, Md Shahid; Begum, Momotaj; Islam, Md Kabirul; Talukder, Md Shah Alam; Ehsan, Md Toufique (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: The purpose of study was to compare Swenson & Soave-Boley procedure in the staged operative treatment of Hirschsprung's Disease (HD). Methods : During 16 months of study period, 25 patients of histopathologically confirmed HD were selected for staged operative treatment, following certain inclusion & exclusion criteria & were admitted & operated at DSH; after completion of all stages operation they were followed up & studied under two groups : staged Swenson procedure (Group-A; na=13) & staged Soave-Boley procedure (Group-B, nb=12). They were similar for age, sex, body weight, reselected length of aganglionic segment & postoperative follow up. The level of ganglionosis was assessed from marking biopsy. Preoperative & postoperative observations of Swenson procedure were analyzed & compared with those of Soave-Boley procedure in the staged operative treatment of HD statistically (unpaired ât' test & Ï2 test) Results : For group A (Swenson procedure) the operative time was significantly lesser (unpaired ât' test : P < 0.01) than for the group B (Soave-Boley procedure). First bowel movement after colostomy closure was also significantly lesser in duration in Swenson procedure (Ï2 Â test :P < 0.05). DOI = 10.3329/jom.v9i1.1420 J MEDICINE 2008; 9 : 16-19 Â